Effects of Short-time High Concentration CO2 Treatment on Keeping Green and the Physiological Quality of Oilseed Rape during Storage - Huimin DUAN; Mengfei PENG; Xuxin ZHANG; Lixiang DAI; Jiaxuan ZHENG; Xia LIU (Shipin gongye ke-ji)
Short-time gas stimulation could induce resistance in fruits and vegetables, prolonging their shelf life and improving their quality during storage. To investigate the effect of high concentration (50%, 70%, 90%) carbon dioxide (CO2) short stimulation (30 min) on keeping green color and preservative quality, the oilseed rape color, yellowing index, chlorophyll content, respiratory intensity, ethylene release, polyphenol oxidase (PPO) peroxidase (POD), weight loss rate, hardness, vitamin C (VC) content, soluble solids content (SSC) and sensory quality were investigated during 20 d storage at 4±0.5 ℃. Results showed that the high-concentration & short-time CO2 treatment could effectively maintain the overall appearance quality of oilseed rape, delayed the occurrence of yellowing, increased chlorophyll content (P<0.05), and inhibited the increase of the yellowing index (P<0.05), among which, 90% CO2 treatment group showed the best effect. On the 20 d of storage, the total chlorophyll content of 50% CO2, 70% CO2, and 90% CO2 treatment groups was 10.85%, 17.46%, and 25.08% higher than the control group, respectively. Meanwhile, the CO2 stimulation treatment significantly weakened the respiratory intensity and ethylene release of oilseed rape during storage and inhibited the activity of PPO and POD. Furthermore, short-time CO2 treatment delayed the increase of weight loss rate and the decrease of hardness, maintained high VC content and SSC and greatly improved the score of sensory quality. On the whole, the 90% CO2 treatment possessed the best and most obvious effect for oilseed rape greening, extending the storage period to 20 d compared to the shorter shelf life (2~3 d) at room temperature. The study provides a theoretical basis for the development of oilseed rape green preservation technology.